Filipino Teachers' Mental Health Amidst the Covid-19 Pandemic - Pekas, Monette G.; Santos, Ferdinand S.; Recede, Reynald Alfred A.; Rosa, Marivic Agbuya Dela (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
The study investigated the problems that adversely affect the mental health of Filipino teachers during the time of Covid-19 pandemic. The results of the study revealed various ways teachers cope with their problems on mental health. Family and other forms of social support, recreational, and spiritual activities have always been beneficial in these challenging times and a lot of studies has proved its effectiveness on dealing with mental health. However, aside from these coping strategies, teachers have proven themselves to be flexible enough to find ways for them to feel much better. The study also proves that teachers are resilient in dealing with their problems. They acknowledged their difficulties, yet they also manage and divert their focus into something more positive and productive. It is also noteworthy that teachers are less likely to experience pandemic fatigue since they always try to be obedient with the safety precautions mandated by the government considering that it is for their own sake. It is recommended that teachers who are about to return to face-to-face classes or onsite reporting be subjected to counseling before they go back to pre-pandemic work set-up so that the delivery of quality education will be ensured as we gradually accept the new normal in the field of education.